The Impact of excluding the death penalty application in the Rome Statute to the decisions of the International Criminal Court - Saleh Abbas, Mahdi; Rady Mohammed, Fadel; Kazem Talib, Zainab (International Journal of Psychosocial Rehabilitation, 2020)
That life is a gift of Heaven to the human being, absolutely, this gift cannot be stolen by anyone, thus, most of the heavenly and statutory laws came to regulate these punishments as it is one of the harshest penalties imposed on individuals because it removes them from the existence, as most state legal legislations tend to limit and reduce them to the maximum extent possible, that is limited to serious criminal cases which threaten world peace and severe crimes, that its application is compatible with the requirements of justice in not implementing it with children or pregnant women, the arguments which was presented by the supporters of both ideologies, the ideology of retaining the death penalty, while the ideology of concealing the death penalty remains subject to analyze the opinions and ideas all of the supporters and opponents of the death penalty. That the countries that have ratified the Rome Statute of the permanent international criminal court and whose charter is devoid of applying the death penalty to crimes that the International Court is competent to consider, also countries that did not want to join the Rome Statute due to the non-application of the death penalty are among the sanctions which was imposed by the court which it is called upon to take the initiative in reaching a solution in which justice satisfies the victims and the people who are victimized from the civilians and others who fall victim to the horrific and dangerous crimes, which it constitutes a threat to international peace and security.